Students' mental models for molecule shapes concepts: A multiple-representation perspective - Erlina Azmi Siregar; Antuni Wiyarsi (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2023)
This research aims to explores the mental model of high school students on the concept of molecular shape from the aspects multiple representation. This research used explorative survey with qualitative approach involving 20 participants selected using the purposive sampling. The data analysis carried out in this study was iterative content analysis to determine a consistent pattern in the participants' answers. The results of this study are as follows there are 33% of students with the target mental model (MMT) category from the symbolic representation aspect on the concept of writing electronic configurations, writing Lewis structures and determining the number of PEB and PEI, 5% of students with the target mental model (MMT) category from the submicroscopic representation aspect on the concept of VSPER theory while on the concept of compound polarity from the macroscopic representation aspect, 35% of students. This is due to the large number of students who have mixed mental model (MMC) and alternative mental model (MMA) categories. In addition, there were 2 students who had an unexplored mental model (MMTT). The low mental model of students is due to the low understanding of students towards multiple representation on the concept of molecular shapes.